MODERN PROBLEMS OF LEGISLATIVE REGULATION OF AN INTERNAL CONTROL - E. N. Kolesnikova (Вестник университета)
The current legislative approaches to understanding the essence and implementation of internal control procedures by economic entities have been systematized. The approach to understanding the essence of internal control as an element of the company’s accounting system that prevails in departmental and industry regulations on accounting in the Russian Federation has been critically analyzed. The historical digression of the development of understanding of the term “internal control” has been presented and its connection with the subjects of control has been proved. The transformation of understanding of the essence of internal control, which is contained in the regulatory legal acts of the USSR and the Russian Federation, from a subjective approach to a simple process approach has been traced, in accordance with the needs of business entities. The ways of improving the legislative framework of internal control have been outlined.